2009
DOI: 10.1111/j.1365-2133.2009.09440.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of skin barrier function and sensory nerve electric current perception threshold between IgE-high extrinsic and IgE-normal intrinsic types of atopic dermatitis

Abstract: Background Two types of atopic dermatitis (AD) have been proposed, with different pathophysiological mechanisms underlying this seemingly heterogeneous disorder. The extrinsic type shows high IgE levels presumably as a consequence of skin barrier damage and feasible allergen permeation, whereas the intrinsic type exhibits normal IgE levels and is not mediated by allergen-specific IgE. Objectives To investigate the relationship between pruritus perception threshold and skin barrier function of patients with AD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 31 publications
(51 reference statements)
4
64
0
2
Order By: Relevance
“…This suggestion may be supported by the observation that CPT was significantly correlated with skin surface hydration and inversely with transepidermal water loss in intrinsic atopic dermatitis, as well as with the VAS scoring of itch in extrinsic atopic dermatitis [42]. Our group also observed a significant correlation between CPT and pruritus severity.…”
Section: Measurement Of Itch Thresholdsupporting
confidence: 77%
See 2 more Smart Citations
“…This suggestion may be supported by the observation that CPT was significantly correlated with skin surface hydration and inversely with transepidermal water loss in intrinsic atopic dermatitis, as well as with the VAS scoring of itch in extrinsic atopic dermatitis [42]. Our group also observed a significant correlation between CPT and pruritus severity.…”
Section: Measurement Of Itch Thresholdsupporting
confidence: 77%
“…However, not all studies were able to demonstrate [41]. Accordingly, Mori et al observed no statistically significant difference in CPT among extrinsic atopic dermatitis, intrinsic atopic dermatitis and normal controls [42]. In contrast, our group found an even higher sensory threshold to electric current stimulation in patients with atopic dermatitis or psoriasis than in healthy volunteers, although no significant differences were found between subjects with atopic dermatitis and psoriasis [43].…”
Section: Measurement Of Itch Thresholdmentioning
confidence: 89%
See 1 more Smart Citation
“…Skin sensitivity to electric current is decreased in patients with extrinsic atopic dermatitis but not in patients with the intrinsic form. This phenomenon appears to be related to an impaired skin barrier in patients with the extrinsic form [77]. In contrast to healthy subjects, neuroselective transcutaneous electrical stimulation preferentially evokes itch in atopics [78].…”
Section: Atopic Dermatitis and Skin Neurophysiologymentioning
confidence: 94%
“…The intrinsic form tends to develop in older patients and filaggrin mutations are not a characteristic of this form [8]. Studies investigating skin barrier function in patients diagnosed with intrinsic AD have shown that normal function and sensory reactivity to external stimuli is retained in these individuals, which is different from patients with the extrinsic form [9]. Immunologically, lower expression of T helper (Th)2 cytokines such as Interleukin (IL)-4, 5, and 13 are found in affected individuals.…”
Section: Atopic Dermatitis: Comparative Observationsmentioning
confidence: 99%